Pengaruh Social Media Marketing Terhadap Customer Engagement Pada Skincare Merek Somethinc Survey Pada Followers Instagram Somethinc - Agung Dwianto; Stefany Bororing (Fakultas Ekonomi & Bisnis Universitas Paramadina, 2023)
Social media provides an additional option for marketers to track consumer attention to build brand awareness and consumer engagement. A number of companies also use social media as a forum to accommodate consumer opinions, criticisms, and input. The purpose of this study is to test whether there is an effect of Social Media Marketing on Customer Engagement. The research design used in this research is a quantitative approach. The sample taken in this study was 100 Instagram followers @somethincofficial. The data collection technique used in this study used a survey method using a questionnaire. The results show that Social Media Marketing (X) has a regression coefficient value of 0.861 and a significance value (Sig.) 0.000 in the Coefficientsa table with a value of (degree of significance) 0.05 meaning 0.000 <0.05 or there is a significant effect and the t test shows 7.554 > t. This means that Social Media Marketing has a positive and significant effect on Customer Engagement.